Digitising diabetes education for a safer ramadan: design, delivery, and evaluation of massive open online courses in ramadan-focused diabetes education - Mackenzie, Scott C.; Dickson, Jane; Salma, Mehar; Mohd Yusof, Barakatun Nisak; Adhari, Alsemi; Bilal, Aksi; Stage Baxter, Mats; Bickerton, Alex; Bharaj, Harnovdeep Singh; Conway, Nicholas; M. Cumming, Kirsten; Lim, Lee-Ling; et al. (Elsevier, 2024)
Aims Ramadan-focused diabetes education is critical to facilitate safer Ramadan fasting amongst Muslim people living with diabetes. We present the design, delivery, and evaluation of two parallel massive open online courses (MOOCs) in Ramadan-focused diabetes education for people with diabetes and HCPs.